Detection of antibodies against to Brucella abortus, Leptospira spp. and Apicomplexa - Konrad, José Luis (2013)
Water buffalo industry has become a profitable activity worldwide, including the Northeast of Argentina (NEA). However, research on diseases affecting this species is scarce. The aim of the present study was to detect antibodies against Brucella abortus, Leptospira spp., Neospora caninum, Toxoplasma gondii, and Sarcocystis spp. in 500 water buffalo cows from five ranches (100 animals each) in the NEA. Serum samples were tested for B. abortus by fluorescence polarization assay, Leptospira spp. By microagglutination test, and N. caninum, T. gondii, and Sarcocystis spp. by indirect fluorescent antibody tests. Overall, the proportion of seropositive animals was 6.4, 22.2, 42.2, 25.4, and 50.8 % for brucellosis, leptospirosis, neosporosis, toxoplasmosis, and sarcocystosis, respectively. The proportion of seropositive animals for all diseases was statistically different among herds (p<0.05). Statistical differences were also detected among age groups for brucelosis and neosporosis (p<0.05). The detection of specific antibodies to B. abortus, Leptospira spp., and several Apicomplexa protozoans in water buffaloes in the NEA is reported in this study.